Experimental and Numerical Investigation of Flow Measurement Mechanism and Hydraulic Performance of Portable Pillar-Shaped Flumes in Rectangular Channels - Bin Sun; Lei Yang; Shun Zhu; Quan Liu; Chao Zhang; Jinping Zhang (Shock and Vibration)
Based on the principle of the critical flow and standard k-ε three-dimensional turbulence model, experiments and simulations were performed on a portable pillar-shaped flume with three contraction ratios under 12 working conditions. By combining the numerical simulations with the experiments, the theoretical stage-discharge formula of the portable pillar-shaped flume was developed, and the variations in the Froude number, backwater height, critical submergence, head loss, and velocity distribution were examined. The simulation data obtained from the standard k-ε three-dimensional turbulence model are in good agreement with the experimental results, with a maximum error of 8.65%. The maximum error in the difference between the theoretical stage-discharge formula and the measured value is 4.74%. The upstream Froude number is less than 0.5, and critical submergence is between 0.73 and 0.96. Compared to airfoil pillar-shaped flumes, the portable pillar-shaped flume had a significantly smaller head loss and backwater height. Finally, the portable pillar-shaped flume can be used for flow measurement and has the advantages of high measurement accuracy, low backwater height, and small head loss.